Response spectrum analysis of medium rise buildings subjected To a far-field earthquake - AWALl, MOHD SHAHRIN (Universiti Teknologi PETRONAS, 2008)
Normally in Malaysia, lateral force that is taken into consideration in design is wind load. Tremors felt by Malaysians from the long distance Sumatran Earthquake on the 26th December 2004 was a "wake up call" for engineers, architects, local authorities and etc to accept the importance of understanding potential seismic hazard that can occur to building and others structure. Seismic loading requires an understanding of the structural behavior under large inelastic, cyclic deformation due to inertial forces of the building mass induced by the shaking of its foundation. The main problem caused by earthquake to building is vibration. Thus, the damage on building is not caused by seismic ground motion but internally generated inertial forces caused by vibration of the building mass. Based on the simulation done using Staad-Pro sofuvare on standard school building design in Malaysia due to Response Spectrum Acceleration of far-field earthquake, this research conclude that our school building is still safe under far-field earthquake loading.